2017
DOI: 10.1007/s12671-017-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mindfulness to Teachers: a Systematic Review and Narrative Synthesis

Abstract: School teachers report high levels of stress which impact on their engagement with pupils and effectiveness as a teacher. Early intervention or prevention approaches may support teachers to develop positive coping and reduce the experience and impact of stress. This article reviews research on one such approach: mindfulness-based interventions (MBIs) for school teachers. A systematic review and narrative synthesis were conducted for quantitative and qualitative studies that report the effects of MBIs for teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
138
0
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(181 citation statements)
references
References 56 publications
11
138
0
16
Order By: Relevance
“…The present study is the first to investigate to what extent mindful- previous meta-analyses, both for the general population and in-service teachers (Emerson et al, 2017;Hofmann et al, 2010;Hwang et al, 2017;Klingbeil & Renshaw, 2018;Lomas et al, 2017), were largely replicated. It should, however, be noted that increases in distraction appeared to partially go back to teacher effects-groups taught by author 1 demonstrated higher increments than groups taught by the other authors, independent from the respective curriculum (mindfulness or awareness activities).…”
Section: Discussion/con Clus Ionsmentioning
confidence: 82%
See 3 more Smart Citations
“…The present study is the first to investigate to what extent mindful- previous meta-analyses, both for the general population and in-service teachers (Emerson et al, 2017;Hofmann et al, 2010;Hwang et al, 2017;Klingbeil & Renshaw, 2018;Lomas et al, 2017), were largely replicated. It should, however, be noted that increases in distraction appeared to partially go back to teacher effects-groups taught by author 1 demonstrated higher increments than groups taught by the other authors, independent from the respective curriculum (mindfulness or awareness activities).…”
Section: Discussion/con Clus Ionsmentioning
confidence: 82%
“…Although no mindfulness‐based benefits were found for suppression, self‐focused rumination, general, and anxious mood, this hypothesis can be regarded as widely corroborated because superior development of the active controls over the passive controls was not observed at all. Hence, results of previous meta‐analyses, both for the general population and in‐service teachers (Emerson et al, ; Hofmann et al, ; Hwang et al, ; Klingbeil & Renshaw, ; Lomas et al, ), were largely replicated. It should, however, be noted that increases in distraction appeared to partially go back to teacher effects—groups taught by author 1 demonstrated higher increments than groups taught by the other authors, independent from the respective curriculum (mindfulness or awareness activities).…”
Section: Discussion/conclusionmentioning
confidence: 84%
See 2 more Smart Citations
“…Good et al 2015;Klatt et al 2009), and their effectiveness in reducing stress been indicated (Allen et al 2015;Hyland et al 2015) among working adults exposed to high occupational stress, including doctors, nurses and other healthcare professionals (e.g. Bazarko et al 2013;Irving et al 2009; Martín-Asuero and García-Banda 2010); teachers (Emerson et al 2017); those working in occupations with high emotional labour (Hülsheger et al 2013); and with indices of poor mental health (Huang et al 2015).…”
Section: Introductionmentioning
confidence: 99%